Diffusion Tensor Tractography Imaging in a Case of Acute Brain Stem Infarct - Nilgül Yardımcı; Hakan Ulubay; Kamil Topalkara; Barış Diren (Türk Nöroloji Dergisi, 2009)
Diffusion tensor tractography enables graphical reconstruction of the white matter pathways in the brain and quantitative study of white matter integrity. With this method virtual dissection of the living human brain can be performed. This technique has many potential clinical applications in neurological disorders, including the investigation of stroke. We present tractography findings of a patient that had an acute ischemic infarct in the brain stem. We aimed to report the disintegration of the white matter tracts at the infarct location in vivo, as well as the associated clinical symptoms. The current use of tractography in neurological disorders shows that it has the potential to improve our understanding of the damage and recovery process in diseases of the brain and spinal cord. From a clinical point of view tractography might be used to test new hypotheses, and to provide important new insights into the organization of the brain and the effects of brain disorders